2014
DOI: 10.1590/0104-1169.3186.2388
|View full text |Cite|
|
Sign up to set email alerts
|

Reports of violence against women in different life cycles

Abstract: Objective to analyze the reports and factors associated with violence against women.Method this was a cross-sectional, exploratory and analytical study with information about the cases of reported violence, extracted from the Civil Police Report Bulletin, in a mid-sized city in Minas Gerais, Brazil. Results out of the 7,487 reports of violence against women, it was found that 44.6% of the cases were threats, 28.5% aggression, 25.1% bodily injury, 1.1% rape, and 0.7% some other type of injury. In the bivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
20

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 22 publications
0
19
0
20
Order By: Relevance
“…4,13 The average age of the victims was 35.72 (standard deviation -SD = 12.98; minimum 15 years; maximum: 94 years). Other studies developed in Brazil reported that adult women, generally between 20 and 49 years of age, represent the main victims of violence.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4,13 The average age of the victims was 35.72 (standard deviation -SD = 12.98; minimum 15 years; maximum: 94 years). Other studies developed in Brazil reported that adult women, generally between 20 and 49 years of age, represent the main victims of violence.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies developed in Brazil reported that adult women, generally between 20 and 49 years of age, represent the main victims of violence. 4,16 This age range is characterized by an important life stage of the women, with relation to their reproductive period and their attention and care for their children. A participant population survey from Multi-country Study on Women's Health and Domestic Violence against Women, which included 790 women who live with children from 5 to 12 years old, residents of the municipality of São Paulo, SP, and in Zona da Mata in Pernambuco, showed that there can be repercussions of the violence against the women in the behavior of the children, indicating the need to adopt effective measures to confront it.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations